The role of metabolic therapy with trimetazidine in effort tolerance in patients with ischemic heart disease - Una Suljić; Besim Prnjavorac; Tamer Bego; Maja Malenica; Tanja Dujić; Irfan Prnjavorac; Adlija Čaušević; Lejla Šaranović (Medicinski glasnik, 2018)
Aim: To investigate whether or not additional treatment of ischemic heart disease with trimetazidine could improve effort tolerance and overall quality of life of patients with ischemic heart disease. Methods: The study included 200 patients with ischemic heart disease. The sample was divided into 2 randomly selected groups: experimental and control group. The diagnostic procedures included: trade-mill test according to Bruce protocol, heart ultrasound for assessment of ejection fraction, test for the assessment of quality of life and subjective problems (Short Form SF 36). Patients were tested for time of discharge from hospital, after 6 and 12 months, including re-evaluation of the overall condition of the previous period. Results: Patients have been tested for the tolerance of effort with the measurement Metabolic Equivalent of TASK (METs), which is the equivalent of physical labor. Patients treated with trimetazidine since the time of hospital discharge achieved an average of 3.68, after 6 months 5.68, and after 12 months 7.79 METs. The control group achieved 3.68, 3.59 and 3.87 METs, respectively. Using Mann-Whitney test no difference at discharge time (p=0.880), but after six and twelve months there was some difference (p<0.001). Results: of ejection fraction measured by echocardiography were similar. No difference between the two groups with regard to time of discharge (p=0.821, but p<0.001 after six and twelve months, respectively). Conclusion: Patients treated with conventional therapy including trimetazidine have better tolerance to effort and better ejection fraction on heart ultrasound examination in comparison with those treated without trimetazidine, so trimetazidin improve the metabolic balance of heart muscle.
Keywords: METs; ergometry; echocardiography; quality of life with heart ischemia